Digital Public Sphere: Message Construction of Menfess Accounts Within an Islamic Communication Framework - Uli Susanti Sri Awan; Suhendri Suhendri; Ricka Adelia Munthe (PERSPEKTIF: Journal of Social and Library Science, 2026)
Social media proliferation has reshaped the digital public sphere into a new arena for social justice discourse, including Islamic communication practices. Menfess accounts, anonymous message channels on Instagram and Twitter, have become a distinctive phenomenon where da'wah, social critique, and justice narratives are constructed without disclosing the sender's identity. This study maps the message-construction mechanisms of menfess accounts and examines their representation through three Qur'anic communication principles: qaulan sadida, qaulan baligha, and qaulan masyura. Employing a qualitative approach grounded in Hjarvard's mediatization theory, the research analyzed 50 menfess messages on social justice from January to March 2026 through digital observation and content analysis. Findings reveal three dominant patterns: an anonymous-narrative pattern leveraging identity invisibility for critique free from authority pressure; a dialogical pattern reflecting the shura principle to cultivate public reasoning; and a communicative-ethics pattern that consistently internalizes qaulan sadida, qaulan baligha, and qaulan masyura. The results affirm that menfess accounts function as a democratic justice arena, resonant with an Islamic-inflected reading of Habermas's public sphere. This study enriches contemporary Islamic communication theory and offers practical guidance for da'wah media managers designing inclusive, justice-oriented digital spaces.